" The impact of the war on Syria on the level of economic and social empowerment of rural women in the Haffa region" - محمد, نغم; غسان يعقوب; منذر خدام (Latakia University Journal -Biological Sciences Series, 2025)
The research aimed to identify the social and economic effects of the war on Syria on rural women in the Haffa region, and to analyze the challenges and difficulties facing rural women in the Haffa region as a result of the war and its impact on their empowerment. To achieve the research objectives, a random sample of 384 rural women in the Haffa region was taken, and the necessary data for the research was collected by designing a questionnaire designed for this purpose according to the personal interview method with sample members. The research adopted the descriptive analytical approach to analyze and describe the sample members' answers to the questionnaire questions using frequency tables and percentages. The quantitative approach was also used to test the research hypotheses using appropriate tests such as the Likert scale, analysis of variance (ANOVA) using the statistical program SPSS.25. The results of the analysis of the economic and social effects of the war on Syria indicated the existence of many challenges facing the empowerment of rural women in the research area. On the economic level, the deterioration of the standard of living and the economy led many young people to emigrate and work in order to support their families, which placed the greatest burden on women who were forced to bear additional responsibilities to manage their families' affairs. On the social level, many services were negatively affected by the war, such as the decline in health services, frequent interruptions of drinking water, and electricity rationing. These challenges directly affected the lives of rural women and their ability to fulfill their family responsibilities. The results of the research hypothesis testing also indicated that there was a statistically significant effect of the war on the level of economic and social empowerment of rural women in the Haffa area at a significance level of 0.05, which confirmed the sensitivity and weakness of rural women's economic and social empowerment to changes and crises.